A claim of her own [large type] - Whitson, Stephanie Grace (Center Point Pub., 2009)
Determined to put the unspeakable circumstances of her past behind her, twenty-year-old Mattie O'Keefe travels to Deadwood, South Dakota, in search of her brother, whose letters boast of making a fortune in the gold fields.